Influence of exposure conditions on the values of strength and absorption in the soil stabilized with lime and rice husk ash - Alcantara, M. A.M. [UNESP]; Fernandes, L. L. [UNESP]; Lollo, J. A. [UNESP]; Lima, D. C. (My University, 2013)
The article presents a study on the influence of exposure conditions on strength and absorption in soil stabilized with lime and rice husk ash. A soil classified as A-4 and CL, known as Red-Yellow Podzol, a hydrated lime and a crystal-type burnt rice husk ashes were used throughout the study. The laboratory testing program encompassed compaction of specimens of soil and its mixtures with lime content of 8% enriched with ash contents of 5% and 10% of the soil dry weight in the Normal Proctor Energy. The specimens were moist-cured for 28 days and then subjected to different exposure conditions, including curing in kiln oven, fully exposed and immersed in water. After curing the specimens were subjected to compressive strength tests with and without previous 24 h immersion in water, and also to absorption tests. Results showed the advantages of using ash as an auxiliary additive in soil-lime mixtures to promote mechanical strength increase and its long-term maintenance, as well as reducing the influence of saturation on compressive strength. Water immersion promoted the best mechanical strength increase, and water absorption increased with the increasing percentage of ash and with the curing time of the mixtures.
Keywords: Mechanical strength; Soil mixtures cure; Soil-lime; Soli-lime-ash; Stabilized soil; Water absorption